Neglected lunate dislocation presenting as carpal tunnel syndrome - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2015)
Most of carpal tunnel syndrome cases are idiopathic, and secondary causes are so rare that can be easily missed. We present a patient with neglected undiagnosed lunate dislocation compressing on median nerve causing its signs and symptoms.
Keywords: Etiology; hand; lunate dislocation; median nerve; syndrome; trauma; unilateral carpal tunnel syndrome